Isolasi dan Identifikasi Sterol dari Ekstrak n-heksana Daun Meniran Hijau Phyllanthus niruri L. (Euphorbiaceae) - Muharram, .; Jannah, Nur (Fakultas MIPA UNM, 2009)
One of the secondary metabolite, namely a sterol had been iosolated from the n-hexane extract of Phyllanthus niruri L leaves. This compound was obtained by isolation that consist of extaction, fractionation, purification, and identification. The identification covers the melting point test, thin layer chromatography and Liebermann-Burchard test. The research results show that the compound is white needle crystal with the malting point 120-122â°C and positive with Lieberman-Burchard reagens that give blue-green coulor. This compound have not yet been established, because it must be evaluated by spectroscopy.methods. Â Keywords: isolation, Phyllanthus niruri L., sterol, Liebermann-Burchard reagent, spectroscopy method